EFFECT OF CLASSICAL MUSIC THERAPY ON THE ANXIETY LEVEL OF HEMODIALYSIS PATIENTS AT THE PKU MUHAMMADIYAH HOSPITAL OF SURAKARTA - Muhammad Luqman Prihananda; Arina Maliya; Kartinah - (Universitas Muhammadiyah Semarang, 2014)
Hemodialysis is a process that is used in patients with acute ill disease and require short-termdialysis therapy or patients with end-stage renal disease. Obtained data from PKUMuhammadiyah Hospital of Surakarta hemodialysis therapy program measures the first timethis year (October 2012-February 2014) is a 472 hemodialysis, in February 2014 as many as 43patients. Overcoming anxiety in these hemodialysis patients, nurses need to provide treatmentthat relaxation therapy, which one using classical music. Classical music is a medical therapythat uses music where the goal is to enhance or improve the physical, emotional, cognitive, andsocial for individuals of all ages. The purpose of this research was to determine the effect oftherapy there any classical music on anxiety levels of hemodialysis patients at the PKUMuhammadiyah Hospital of Surakarta. This research uses a quasi-experimental withnonequivalent control group design. The population in was all patients undergoing hemodialysistherapy program at PKU Muhammadiyah Surakarta totaling 43 patients, and for the studysample is 30 respondents for both groups, this research uses technique accidental sampling.Research instrument such as the Hamilton Rating Scale-Anxeity (HRS-A). Analysis of using theIndependent T-Test test and Paired T-Test. The conclusion of this research there are significantclassical music therapy on anxiety levels of hemodialysis patients at the PKU MuhammadiyahHospital of Surakarta.Keywords: Hemodialysis, Anxiety, Classical Music Therapy